Relationship Between Team Identification and Consumption Behaviors: Using a Meta-Analysis - Kwon, Hyungil; Pyun, Do Young; Lim, Seung Hyun (Frontiers in Psychology, 2022)
Abstract Purpose - The purpose of this study was to conduct a comprehensive literature review and a meta-analysis on team identification, particularly its relations with both intentions to attend games and to purchase licensed merchandise. Design/methodology/approach - Past literature was searched through several electronic databases including SPORTDiscus using relevant keywords. Thirteen studies for team identification-intention to attend sport games and nine studies for team identification-intention to purchase licensed merchandise meeting the selection criteria were identified. A random effect model was used to conduct a meta-analysis. Funnel plot and Egger’s test were conducted to test publication bias, followed by fail-safe N to examine the stability of the estimates. Findings - The results showed that the total effect size values for the relationships between team identification and intentions to attend games and to purchase licensed merchandise were .39 and .42 respectively, which were classified as a medium-large effect size. The medium-large sized effects can be considered sufficient magnitudes of the relationships, confirming the predictive power of team identification when it pertains to sport consumers’ behaviours. Originality- While team identification is one of the most popularly studied topics in spot marketing literature, the findings related to its impacts on consumer behaviour is fragile. This meta-analysis contributes to fill the current research gap by quantifying predictive accuracy of team identification.